2009
DOI: 10.1016/j.jtcvs.2008.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral internal thoracic artery on the left side: A propensity score–matched study of impact of the third conduit on the right side

Abstract: In patients with triple-vessel disease undergoing first isolated coronary artery bypass grafting, supplementary venous grafts seem to provide more stability than gastroepiploic artery, which may even impair long-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…Moreover, the relatively small sample size can partially account for lack of survival benefit by using the RA. However, the non-significant trend towards lower survival probabilities in the BITA+RA group, also reported by others [4,5] limits the potential role of type beta error in rejecting the hypothesis of the superiority of the RA. Finally, the study was observational on prospectively collected data and selection bias cannot be excluded despite propensity score adjustment.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Moreover, the relatively small sample size can partially account for lack of survival benefit by using the RA. However, the non-significant trend towards lower survival probabilities in the BITA+RA group, also reported by others [4,5] limits the potential role of type beta error in rejecting the hypothesis of the superiority of the RA. Finally, the study was observational on prospectively collected data and selection bias cannot be excluded despite propensity score adjustment.…”
Section: Discussionmentioning
confidence: 70%
“…The right internal thoracic artery (RITA) has been advocated to further improve long term revascularization outcomes [2]. Whether the use of the radial artery (RA) [3][4][5] as third arterial conduit in addition to bilateral internal thoracic artery (BITA) grafting is associated with better survival when compared to BITA plus saphenous vein (SV) remains to be determined with isolated small series reporting conflicting results [6,7].…”
mentioning
confidence: 99%
“…Zacharias et al [15] found a perioperative mortality of 1.3% in patients having total arterial grafting (mean age 60 years), which was significantly better than that for LITA þ saphenous vein grafts (SVG), 1.7% (propensity score matched). Di Mauro et al [16] found an operative mortality of 1.8% in 1015 patients undergoing BITA, and Nasso et al [17] had an operative mortality of 2.2% in 406 BITA patients versus 3% in patients undergoing LITA þ SVG.…”
Section: Perioperative Results For Right Internal Thoracic Artery/bilmentioning
confidence: 99%
“…Grafting the RGEA to the right coronary artery system seems to be efficient in patients with proximal stenosis; 25 however, its therapeutic benefits in terms of late outcomes remain uncertain. 10, 26 Similarly, favorable late outcomes were reported for use of an RA graft and IMA graft in comparison to an SVG and IMA graft in elderly patients. 27 Contrarily, another group reported that use of an RA graft vs. SVG graft did not improve late survival in any age group.…”
Section: Disclosuresmentioning
confidence: 89%